Cultural worldviews and waste sorting among urban Chinese dwellers: the mediating role of environmental risk perception - Cai, Lin; Li, Qingjun; Wan, Erya; Luo, Menglin; Tao, Siwen (Frontiers in Public Health, 2024)
Objective: The waste sorting has received extensive attention in the last few decades. However, research on the mechanism underlying the relationships among cultural worldview, perception of environmental risk, and waste sorting is rather scarce. This study aims to explore cultural worldview, environmental risk perception, and waste sorting among urban Chinese and their mechanisms. Methods: This was a cross-sectional study with 744 urban Chinese residents (371 males and 373 females). A questionnaire was utilized to measure cultural worldview, perception of environmental risk, and waste sorting. Pearson correlation analysis and structural equation modeling were used to examine the relation among cultural worldview, perception of environmental risk, and waste sorting. Results: Waste sorting was relatively insignificant negatively related to fatalism and individualism. The correlation between environmental risk perception and cultural worldviews was negative except for egalitarianism, and the correlation between hierarchy and environmental risk perception was higher than the others, while individualism was higher than fatalism. Heightened environmental risk perception mediates the relationship between egalitarianism and waste sorting. Reduced environmental risk perception mediates the relationship between hierarchy and waste sorting, and mediates the relationship between individualism and waste sorting. Conclusion: These new findings provide an initial support for the mediating roles of environmental risk perception in the relationship between cultural worldview and waste sorting. Both theoretical and practical implications for understanding the psychological mechanisms of waste sorting are discussed.